Bistability in palladium complexes with two different redox-active ligands of orthogonal charge regimes - Kreis, Franka; Poddel'sky, Andrey; Hammermüller, Leon; Bootz, Pascal; Bodenmüller, Franz Anton; Kaifer, Elisabeth; Köhn, Andreas; Himmel, Hans-Jörg (Chemistry - a European journal, 2025)
Electronically bistable molecular coordination compounds are obtained by a combination of two different redox-active ligands with orthogonal charge regimes in square-planar palladium complexes. Thereby, the first complexes are obtained in which two redox isomers are interconverted by interligand electron transfer between a catecholato/semiquinonato (dioxolene) ligand and a redox-active guanidine (GFA) ligand. Experiments in alliance with quantum-chemical calculations indicate that the barrier between the two states is relatively small. Due to the significantly different dipole moments of the two redox isomers, the intramolecular electron transfer can be triggered by variations in the solvent polarity. The energy difference between the two redox isomers and thus the ratio of their formation can be tuned by modifications at the dioxolene and GFA ligands.
Online veröffentlicht: 9. Dezember 2025
Gesehen am 09.02.2026